2021
DOI: 10.3389/fnut.2021.662357
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Dietary Inflammatory Index and Mental Health: A Systematic Review and Dose–Response Meta-Analysis

Abstract: Objective: We aimed to systematically evaluate the association between Dietary Inflammatory Index (DII) and mental health.Methods: We searched PubMed, Embase, and Web of Science from their inception to December 31, 2020. Categorical meta-analysis and dose–response meta-analysis were performed to evaluate the association between DII and mental health.Results: A total of 16 studies were included in this meta-analysis. Compared with the lowest DII category, the highest category was significantly associated with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 90 publications
(65 reference statements)
0
24
2
1
Order By: Relevance
“…Overall, the associations are consistently positive for depression and severe mental illness. They are not as consistent for anxiety (23). So, the results from this study are somewhat inconsistent with previous results.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Overall, the associations are consistently positive for depression and severe mental illness. They are not as consistent for anxiety (23). So, the results from this study are somewhat inconsistent with previous results.…”
Section: Discussioncontrasting
confidence: 99%
“…In addition to the positive association between the DII score and risk of cardiometabolic diseases ( 22 ), a comprehensive evaluation of current evidence indicated that higher DII was associated with an increased risk of common mental health outcomes, including depression, symptoms of anxiety, and distress, as well as schizophrenia in adults ( 23 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent study has demonstrated that dietary inflammatory index (DII) is inversely associated with depression ( 7 ). One meta-analysis showed that a 1-unit increment in DII was associated with an increased risk of 6% for depressive symptoms ( 35 ). Previous research also indicated that increased risk of depression was associated with the Western diet, characterized by consumption of high red and processed meat and refined carbohydrates, and decreased risk of depression with the Mediterranean diet, represented by high amount of fruit, vegetables, and whole grains ( 36 , 37 ).…”
Section: Introductionmentioning
confidence: 99%
“…The finding indicated that a higher DII score was related to the higher risk of depressive symptoms, which in turn, led to sarcopenia independent of the direct effects of DII on sarcopenia. Similarly, our previous meta-analysis showed that a pro-inflammatory diet was associated with an increased risk of common mental health outcomes, such as depressive symptoms, anxiety, distress, and the association presented in a dose-response manner (32). Potential mechanisms underlying the association between DII and depressive symptoms may include oxidant-antioxidant imbalance and modified gut microbiota composition and activity (33,34).…”
Section: Discussionmentioning
confidence: 74%